Evaluation of stereo matching algorithms and dynamic programming for 3D triangulation - Teo, Chee Huat; Manap, Nurulfajar (Springer International Publishing, 2015)
A good result of triangulation or known as Three-Dimensional (3D) is depending on the smoothness of the disparity depth map that obtained from the stereo matching algorithms. The smoother the disparity depth map, the better results of triangulation can be achieved. This paper presents the evaluation of the existing stereo matching algorithms in the aspects of the speed of computational on depth map obtained. The stereo matching algorithms that we applied for experimental purpose are basic block matching, sub-pixel accuracy and dynamic programming. The dataset of stereo images that used for the experimental purpose are obtained from Middlebury Stereo Datasets. This research is to provide an idea on choosing the better stereo matching algorithms to work on the disparity depth map for the purpose of 3D triangulation applications, as the good result of 3D triangulation is depending on how smooth is the disparity depth map can be obtained.